ASPEK PEMIJAHAN IKAN PETEK, Leiognathus equulus, FORSSKAL 1775 (FAM. LEIOGNATHIDAE) DI PESISIR MAYANGAN SUBANG JAWA BARAT [Gonadal Development, Fecundity, and Spawning Seasons of Sliymouth, Leiognathus equulus, Forsskal 1775 (Fam. Leiognathidae) in Mayangan Coastal, Subang, West Java] - Rini Novitriana; Yunizar Ernawati; M. F. Rahardjo (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2004)
Study was done from May to November 2003 in Mayangan coastal, West Java. Fish samples taken once in a month. Laboratory analysis comprises measuring of total length and body weight; sex determination; and morphological and histological observation of gonad maturity. Total samples is 970 fishes, comprises 528 male, 326 female, and 80 indeterminate sexually. Samples is in the size range 45-208 mm total length and 1.38 - 145.7 grams body weight. Presumably, fish spawn every month with peak spawning in August and it attain first maturity at least 88 mm (male) and 95 mm (female). Gonado somatic index (GSI) of male among 0,0105-3,3021%, while female have GSI among 0,2076-6,0658%. In size range 83-208 mm, fecundity is among 1.496-57.845 eggs, and this value have very close relationship with gonad weight. Observation of frequency distribution of eggs diameter show that fish spawn their eggs all at once (total spawner).